EXPANDED HEMODIALYSIS: BASIC PRINCIPLES AND CLINICAL SIGNIFICANCE: EXPANDED HEMODIALYSIS - Petrović, Dejan; Nenadović, Marko; Nikolić, Aleksandra; Stanojević Pirković, Marijana; Kostović, Milica; Drašković, Branislava; Nikolić, Tomislav; Trbojević Stanković, Jasna (Medicinski časopis, 2021)
Expanded hemodialysis is a method of treatment to replace kidney function, which effectively remove uremic toxins of middle molecular weight from the blood patients with the end stage of chronic kidney disease. The two basic principles of removing uremic toxins during an expanded hemodialysis session are diffusion and convection. The basis of diffusion is the concentration gradient, and the basis of convection is internal filtration (covective transport). Increased MCO membrane sieving capacity and high internal filtration provide high clearance of middle molecular weight uremic toxins. Expanded hemodialysis prevents the development of microinflammation, malnutrition, resistance to the action of erythropoietin, amyloidosis, accelerated atherosclerosis and atherosclerotic cardiovascular diseases in the population of patients treated with regular dialysis. The task of the nephrologist is to evaluate the different dialysis modalities that are available and to select the optimal dialysis modality for the treatment of each patient individually /individualization of dialysis treatment/.